PENGARUH WAKTU PENAHANAN PANAS (TIME HOLDING) PADA PROSES TEMPERING TERHADAP KEKUATAN TARIK DAN KEKERASAN BAJA KARBON MENENGAH - indra gunawan (Saintia Fisika, 2013)
In this research, a hardness and tensile strength tested. A test using medium carbon steel with methods quenching, and tempering variying at 30, 60, and 90 minutes, as well as original material. A Testing Machine Type MR - 20 - CT no. 6592 is used for the tensile strength test and Vickers Hardness Tester using the Matsuzawa Seiki no 7104 brand, is used  for the hardness test. First, the original material is heated  at 850 °C which  then is processed in water by quenching. After the quenching process is done, the material is heated again heated again at 400 °C, and a Time Holding process is applied to the heated material variying at 30 minutes, 60 minutes and 90 minutes, and then cooled at room temperature. A result of this research is obtained, the highest reading for  the tensile strength of carbon steel test is the quenching process, which is at 632.98 x 106 N/m2, where as for the hardness of carbon steel is also at the quenching process, which is at 1972.94 x 106 N/m2. Keywords : Hardness, Medium Carbon Steel, Quenching, Tempering, Tensile strength